2018
DOI: 10.1017/inp.2018.8
|View full text |Cite
|
Sign up to set email alerts
|

Seed-Dispersal Ability of the Invasive Perennial Vines Vincetoxicum nigrum and Vincetoxicum rossicum

Abstract: Black swallowwort [Vincetoxicum nigrum (L.) Moench] and pale swallowwort [Vincetoxicum rossicum (Kleopow) Barb.] are perennial vines of European origin that invade natural areas and perennial cropping systems in the northeastern United States and southeastern Canada. Both species reproduce via wind-dispersed seeds in the form of achenes with comas, but little is known about the extent of dispersal of these seeds. We studied the relationship of seed release height (0.75 m, 2 m), wind speed at the time of releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 65 publications
(87 reference statements)
2
15
0
Order By: Relevance
“…We speculate that our results are more supportive of the first hypothesis, particularly because a trade-off between dispersal ability and seed mass has broad support in the literature ( Cappuccino et al 2002 ; Huang et al 2015 ; Tabassum and Leishman 2017 ; DiTommaso et al 2018 ). Although the NSC increased with altitude ( Fig.…”
Section: Discussionsupporting
confidence: 82%
“…We speculate that our results are more supportive of the first hypothesis, particularly because a trade-off between dispersal ability and seed mass has broad support in the literature ( Cappuccino et al 2002 ; Huang et al 2015 ; Tabassum and Leishman 2017 ; DiTommaso et al 2018 ). Although the NSC increased with altitude ( Fig.…”
Section: Discussionsupporting
confidence: 82%
“…Fitting this cumulative frequency distribution to the observed distribution of Δ patches (using the nonlinear least‐squares fitting method as implemented in MATLAB), we obtained a value L = 43 m (nonlinear least‐squares fitting: R adj 2 = 0.79, df = 570, P < 10 −16 ). This corresponds to a mean dispersal distance of π2L= 38 m (e.g., Nathan et al 2012), which is higher than observed for wind‐dispersed seeds of other invasive vine species Vinetoxicum nigrum and V. rossicum (4–17 m, DiTommaso et al 2018), but within the dispersal range observed in the same study (0–80 m DiTommaso et al 2018). The extent of the resulting dispersal kernel is very similar to the dispersal kernel used in a previous study to describe spread of the vine Pueraria montana var.…”
Section: Methodssupporting
confidence: 56%
“…Nonetheless, limited empirical evidence suggests that interindividual height variation might be at least a minor driver of interindividual variation in dispersal, at least for abiotically dispersed species. With anemochory, plant (or seed release) height has been shown to be positively related to dispersal distances in trees (Sinha and Davidar 1992) and herbaceous perennials (Sheldon and Burrows 1973; Weiblen and Thomson 1995; Skarpass et al 2011; Zhang et al 2011; Zhu et al 2016; DiTommaso et al 2018), in some cases relatively strongly (e.g. Zhu et al 2016).…”
Section: Intrinsic Variation: Plant Traitsmentioning
confidence: 99%